One-pot tandem oxidative-wittig olefination of primary alcohols using spent battery material as a heterogeneous catalyst in green solvent GVL - Bankar, Shubham R.; Ghadge, Sambhaji S.; Jadhav, Vrushali H. (Catalysis Letters, 2026)
Extensive global utilization of dry cell batteries resulted in generation of huge amount of battery waste. Up-cycling of spent battery waste material as a heterogeneous catalyst is an emerging area of research. Cathode material from spent dry cell battery (Zinc-carbon) was isolated, acid leached and calcined to obtain BCM-2 which was used as a heterogeneous catalyst for one-pot tandem oxidative-Wittig olefination in & upsih;-valerolactone (GVL) a bio-based green solvent at a temperature of 50 degrees C. Reaction was found to proceed smoothly using an economical catalyst and environment friendly conditions to get olefins in good yield up-to 74%. The catalyst was found to be reusable for four cycles. The reaction was carried out two-steps in one pot using spent battery material as a catalyst in GVL as a solvent under mild reaction conditions and the applicability of catalyst was shown in 13 examples. The catalyst's effectiveness was also assessed in synthesis of (E)-3, 4 `, 5-trimethoxy-trans-stilbene, an intermediate for biologically active Resveratol.
Keywords: One-pot; Oxidation; Spent battery; Wittig olefination